Redes sociais na internet: as comunidades e os blogs como oportunidades para a publicidade e o marketing - Huelsen, Patrícia Giannoccaro Von (2008)
This paper discusses the C2C relations occurring in blogs and communities on the Brazilian Internet as an opportunity to practices of advertising and marketing. Nowadays, the Internet offers much more than just free information, placing itself as a forum for social manifestations, a space where people put forward their opinions, search for identities and interact with friends or even with unkown people. Therefore, companies that usually focus on audiences only, can now interact with their custumers. This paper is meant to provide researchers and marketing agents with support in their efforts to identify these opportunities of interaction. It is a qualitative study, based on the observation of social manifestations and on consistent interviews. Sociology and Marketing are its theoretical grounds. Research has shown that advertising and marketing moves, concentrate on procedures which are very little interactive, with a predominance of the use of banners and links; and that the utilization of public relations and viral marketing also takes place. Research has also pointed out that the nature of interactions that occur on social webs are mainly affective, but the existence of marketing on C2C webs creates relationships driven by other interests, as well. The web turns to be a space not quite predictable, where the roles and identities of consumers and companies are mixed together. Thus, these are the challenges to advertising and marketing posed by social webs: to watch closely these groups manifestations, to measure such interactions and to make use of multilateral actions